2023
DOI: 10.1158/1078-0432.c.6530132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from The B7-H3–Targeting Antibody–Drug Conjugate m276-SL-PBD Is Potently Effective Against Pediatric Cancer Preclinical Solid Tumor Models

Abstract: <div>AbstractPurpose:<p>Patients with relapsed pediatric solid malignancies have few therapeutic options, and many of these patients die of their disease. B7-H3 is an immune checkpoint protein encoded by the <i>CD276</i> gene that is overexpressed in many pediatric cancers. Here, we investigate the activity of the B7-H3–targeting antibody–drug conjugate (ADC) m276-SL-PBD in pediatric solid malignancy patient-derived (PDX) and cell line–derived xenograft (CDX) models.</p>Experiment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In our recent preclinical study using a CD276-targeted ADC (m276-SL-PBD), we observed an objective response rate of 93% in the neuroblastoma cell line-derived and patient-derived xenografts. 19 Importantly, all neuroblastoma PDXs assessed display a strong ADRN signature, so the efficacy of CD276-targeted agents, as well as other preclinical molecules, remains to be determined in MES-dominant neuroblastomas. While antigen loss is a known mechanisms of escape from many immunotherapies, our data suggest that this might largely occur by epigenetic mediated cell state transitions in neuroblastoma and this needs to be considered in ongoing and future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our recent preclinical study using a CD276-targeted ADC (m276-SL-PBD), we observed an objective response rate of 93% in the neuroblastoma cell line-derived and patient-derived xenografts. 19 Importantly, all neuroblastoma PDXs assessed display a strong ADRN signature, so the efficacy of CD276-targeted agents, as well as other preclinical molecules, remains to be determined in MES-dominant neuroblastomas. While antigen loss is a known mechanisms of escape from many immunotherapies, our data suggest that this might largely occur by epigenetic mediated cell state transitions in neuroblastoma and this needs to be considered in ongoing and future clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…For murine efficacy studies, we engrafted CB17 severe combined immunodeficiency (SCID) mice with cell line-derived xenografts (CDXs) or patient-derived xenografts (PDXs) and followed the standard protocol established in the Pediatric Preclinical Testing Consortium (now named Pediatric Preclinical In Vivo Testing, PIVOT). 19 In brief, mice with tumors at enrollment size (0.2-0.3 cm 3 ) received 1 mg/kg of either ADCT-601 or B12-PL1601 via tail vein injection. Studies were performed with N=6 animals per arm and the mice were monitored for 100 days or until their tumor burden reached 2.0 cm 3 .…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other surface proteins have been nominated as candidate immunotherapeutic targets in neuroblastoma, including L1CAM [17], ALK [7,[18][19][20], GPC2 [21], DLL3 [22] and B7H3 [23,24]; however, no non-GD2 directed immunotherapy has to date shown significant anti-tumor activity in patients [25] .…”
Section: Introductionmentioning
confidence: 99%
“…were grown in CB17SC scid -/-female (5-8 weeks) mice following protocols established by the Institutional Animal Care and Use Committee (IACUC) at the Children's Hospital of Philadelphia. Tumors were then removed from mice, dissected into 250 mg sections, washed with PBS, snap frozen in liquid nitrogen, and stored at -80 freezer [23]…”
mentioning
confidence: 99%